STANDING Collaboration: a study protocol for developing clinical standards. Issue 10 (11th October 2017) - Wiles, Louise K; Hibbert, Peter D; Stephens, Jacqueline H; Coiera, Enrico; Westbrook, Johanna; Braithwaite, Jeffrey; Day, Ric O; Hillman, Ken M; Runciman, William B
Abstract : Introduction: Despite widespread availability of clinical practice guidelines (CPGs), considerable gaps continue between the care that is recommended ('appropriate care') and the care provided. Problems with current CPGs are commonly cited as barriers to providing 'appropriate care'. Our study aims to develop and test an alternative method to keep CPGs accessible and up to date. This method aims to mitigate existing problems by using a single process to develop clinical standards (embodied in clinical indicators) collaboratively with researchers, healthcare professionals, patients and consumers. A transparent and inclusive online curated (purpose-designed, custom-built, wiki-type) system will use an ongoing and iterative documentation process to facilitate synthesis of up-to-date information and make available its provenance. All participants are required to declare conflicts of interest. This protocol describes three phases: engagement of relevant stakeholders; design of a process to develop clinical standards (embodied in indicators) for 'appropriate care' for common medical conditions; and evaluation of our processes, products and feasibility. Methods and analysis: A modified e-Delphi process will be used to gain consensus on 'appropriate care' for a range of common medical conditions. Clinical standards and indicators will be developed through searches of national and international guidelines, and formulated with explicit criteria for inclusion, exclusion, time frame and setting. Healthcare professionals and consumers will review the indicators via the wiki-based modified e-Delphi process. Reviewers will declare conflicts of interest which will be recorded and managed according to an established protocol. The provenance of all indicators and suggestions included or excluded will be logged from indicator inception to finalisation. A mixed-methods formative evaluation of our research methodology will be undertaken. Ethics and dissemination: Human Research Ethics Committee approval has been received from the University of South Australia. We will submit the results of the study to relevant journals and offer national and international presentations.